2020
DOI: 10.3390/cells9010144
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Tumor Metastasis through Suppressing Hsp90α Secretion in an AMPKα1-PKCγ Dependent Manner

Abstract: Metformin has been documented in epidemiological studies to mitigate tumor progression. Previous reports show that metformin inhibits tumor migration in several cell lines, such as MCF-7 and H1299, but the mechanisms whereby metformin exerts its inhibitory effects on tumor metastasis remain largely unknown. The secreted proteins in cancer cell-derived secretome have been reported to play important roles in tumor metastasis, but whether metformin has an effect on tumor secretome remains unclear. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Mouse monoclonal antibody against human Hsp90α was developed by our laboratory whose specificity and efficiency were verified [ 11 , 25 ]. Recombinant human Hsp90α protein was provided by Protgen (Yantai, China) [ 58 , 65 ]. Antibodies against LYVE-1 (ab14917), LRP1 (ab28320), CXCL8 (ab110727) and β-actin (ab8227) were from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse monoclonal antibody against human Hsp90α was developed by our laboratory whose specificity and efficiency were verified [ 11 , 25 ]. Recombinant human Hsp90α protein was provided by Protgen (Yantai, China) [ 58 , 65 ]. Antibodies against LYVE-1 (ab14917), LRP1 (ab28320), CXCL8 (ab110727) and β-actin (ab8227) were from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Studying breast cancer-derived cell lines, Stivarou et al found that extracellular HSP90 was overexpressed in mammosphere-forming cell cultures, while the mammospheres were enriched with CSC-like CD44(+)/CD24(−/low) cells; the authors suggested that extracellular HSP90 represents a phenotypic marker of breast CSCs [106]. It was recently reported that the secretion of HSP90 by breast CSCs is required for cancer-related signaling pathways and breast tumor xenograft growth in mice [109]; inhibiting the HSP90 secretion and/or extracellular HSP90 functions was therefore suggested as a potential approach to CSC-based therapy of cancer.…”
Section: Extracellular Hsp90mentioning
confidence: 99%
“…As for the latter, the inhibition of HSP90 secretion from CSCs by means of multifunctional magnetic nanoparticles (MNPs) seems to be a very promising approach because this MNP-exerted effect was accompanied by sensitization of CSCs to thermotherapy and chemotherapy [107]. Gong et al have shown that metformin, a drug against type 2 diabetes, can suppress such an EMT/cancer stemness-associated phenomenon as metastasis occurrence by inhibiting HSP90α secretion in a phosphorylation-dependent manner involving AMP-activated protein kinase α1 and protein kinase Cγ [109].…”
Section: Targeting Extracellular Hsp90mentioning
confidence: 99%
“…In addition, metformin augmented Foxo3a nuclear localization and protein stabilization to active Foxo3a with IKKβ repression and MDM2 phosphorylation involvement, leading to the level of E-cad increase [42]. For protein kinase Cγ (PKCγ), which was attenuated after AMPK-α1 phosphorylation, it modulated Hs90α activation [48].…”
Section: Discussionmentioning
confidence: 99%